Forecasting and evaluation for transportation planning (1994)
How do you avoid "black box" mysteriesn Jim Gosnell explores the information foundation and evaluative systems of transportation planning. He examines the complexity, constraints, uncertainty, and methods involved in determining what information is important. This is a practical discussion of how to address decision and information needs for good transportation planning.